Minimal Residual Disease Prior to and After Haematopoietic Stem Cell Transplantation in Children and Adolescents With Acute Lymphoblastic Leukaemia: What Level of Negativity Is Relevant? - Merli, Pietro; Ifversen, Marianne; Truong, Tony H.; Marquart, Hanne V.; Buechner, Jochen; Wölfl, Matthias; Bader, Peter (Frontiers in Pediatrics, 2021)
Minimal residual disease (MRD) assessment plays a central role in risk stratification and treatment guidance in paediatric patients with acute lymphoblastic leukaemia (ALL). As such, MRD prior to haematopoietic stem cell transplantation (HSCT) is a major factor that is independently correlated with outcome. High burden of MRD is negatively correlated with post-transplant survival, as both the risk of leukaemia recurrence and non-relapse mortality increase with greater levels of MRD. Despite growing evidence supporting these findings, controversies still exist. In particular, it is still not clear whether multiparameter flow cytometry and real-time quantitative polymerase chain reaction, which is used to recognize immunoglobulin and T-cell receptor gene rearrangements, can be employed interchangeably. Moreover, the higher sensitivity in MRD quantification offered by next-generation sequencing techniques may further refine the ability to stratify transplant-associated risks. While MRD quantification from bone marrow prior to HSCT remains the state of the art, heavily pre-treated patients may benefit from additional staging, such as using 18F-fluorodeoxyglucose positron emission tomography/computed tomography to detect focal residues of disease. Additionally, the timing of MRD detection (i.e., immediately before administration of the conditioning regimen or weeks before) is a matter of debate. Pre-transplant MRD negativity has previously been associated with superior outcomes; however, in the recent For Omitting Radiation Under Majority age (FORUM) study, pre-HSCT MRD positivity was associated with neither relapse risk nor survival. In this review, we discuss the level of MRD that may require pre-transplant therapy intensification, risking time delay and complications (as well as losing the window for HSCT if disease progression occurs), as opposed to an adapted post-transplant strategy to achieve long-term remission. Indeed, MRD monitoring may be a valuable tool to guide individualized treatment decisions, including tapering of immunosuppression, cellular therapies (such as donor lymphocyte infusions) or additional immunotherapy (such as bispecific T-cell engagers or chimeric antigen receptor T-cell therapy).